Water‐Soluble Biocompatible Copolymer Hypromellose Grafted Chitosan Able to Load Exogenous Agents and Copper Nanoclusters with Aggregation‐Induced Emission. (27th June 2018) - Wang, Zhenguang; Shi, Yu‐e; Yang, Xuming; Xiong, Yuan; Li, Yanxiu; Chen, Bingkun; Lai, Wing‐Fu; Rogach, Andrey L.
Abstract: A water‐soluble, positively charged polymer is obtained by copolymerizing chitosan with hypromellose, and the evaluation of its biocompatibility and the capacity for the loading of exogenous agents is performed. Films based on hypromellose grafted chitosan (HGC) are employed as a matrix to fabricate composite films by dehydration‐triggered aggregation of copper nanoclusters (NCs). The resulting HGC/Cu NC films are transparent and exhibit an aggregation‐induced emission enhancement of copper NCs, with a resulting photoluminescence quantum yield of 42%. The application of these orange emitting films as color converters for fabrication of remote light‐emitting devices is demonstrated. Abstract : Positively‐charged and nontoxic polymer is obtained by copolymerizing chitosan with hypromellose, and employed as a matrix to fabricate biocompatible composite films, which are transparent and show orange emission with a quantum yield of 42%, owing to the aggregation‐induced emission enhancement of copper clusters. Films were used to loadcapacity exogenous agents, and as color converters for remote light emitting devices.